Experiential pedagogy and its links to innovative entrepreneurship: evaluating compulsory entrepreneurship education in Nigeria - Udeozor, Victor Chukwuemeke (2020)
As yet, knowledge of how entrepreneurship education influences innovative entrepreneurs is limited. Examination of extant knowledge on innovative entrepreneurship reveals two specific critical aspects. First, the effect of contextual factors on the innovative intentions is fragmented and evidence from a resource constraint environment is sparse. Besides resource constraint, contextual factors of interest here include whether an entrepreneurship course is compulsory, or whether a university is public or private. Second, the role of experiential pedagogy in the development of innovative capabilities is not fully understood. Even if we accept as valid the utility of experiential pedagogy regarding innovation capabilities, what constitutes experiential pedagogy is not commonly agreed upon. The main objective of this thesis, therefore, is to explore experiential pedagogy and its links to innovative entrepreneurship in a resource constrained environment.